A Video Feedback Intervention for Workforce Development: Exploring Staff Perspective Using Longitudinal Qualitative Methodology. Issue 2 (16th March 2015) - James, Deborah Michelle; Hall, Alex; Lombardo, Chiara; McGovern, Will
Abstract : Background: In this study, we explored the impact of staff training that used video feedback to help staff see the effect of their interactional work with service users. The study was based at a large organization delivering services for children and adults with autism. Materials and Methods: A longitudinal qualitative study with semi‐structured interviews was conducted to explore changes over time in 10 staff participants who received the intervention. Five participants were interviewed twice before they received the video feedback intervention to gauge the degree to which their perspective changed as part of the natural course of their working lives. Results: The results showed that the staff talked differently after they had the intervention. The most notable change was their talk about the service user perspective which was evident after the intervention but not before. Conclusions: The outcomes suggest that the use of video feedback of in situ practice could help staff develop person‐centred work practices.